Construção e caracterização do campo acústico de transdutores ultra-sônico piezoelétrico de polarização variável - Moreira, Danilo Conti (Universidade Federal de São Carlos, 2008)
This work was motivated on the great technological and commercial interest of ultrasonic transducer, capable to generate diffraction controlled ultrasonic beams in the frequency range of kHz up to MHz. As a solution, in this work we proposed the construction of Bessel-like transducers, which have the polarization of the piezoelectric constituent element with a Bessel function profile. As a comparative result, conventional transducers were also built. The conventional modes of vibration, thickness and radial, were characterized, aiming to estimate the potential of these transducers for applications in diagnosis, such as: non-destructive tests or medicalultrasonography. The transducers were based on a poled niobium doped PZT ferroelectric ceramics, with disk shape. The polarization profile, of the concentric electroded rings, of the Bessel-like transducer followed the Bessel function (Jo) profile. The characterizations were based on electromechanical and acoustics techniques for the emission, reception and emissionreception (pulse-echo) modes. To the acoustic characterizations (acoustic field) transducers receivers (hydrophones) were also constructed and calibrated as a function of the frequency, to present a linear response in the frequency range for each transducer. The electromechanical characterization provided the impedance spectrum of the vibration modes, and their respective harmonics, for the transmitters and receivers transducers. The characterization of the transducers acoustic field, for both modes, thickness and radial, has shown that on the Bessel-like transducers the diffraction of the central beam can be controlled and/or reduced, if compared with the conventional, or uniform poled transducer. However, the experimental verification of radial mode pattern of the conventional transducer (in the fundamental mode or in each of its harmonics), showed a natural Bessellike transducer behavior, with a typical Bessel polarization profile. Exploring the radial mode can provide a lower frequency of operation (if compared with the thickness mode), allowing one increase of the penetration depth, besides a decreasing on the ultrasound Rayleigh beam distance, with good collimation and good resolutions. The results of this study shown that ultrasonic transducer with non uniform polarization pattern, especially those of Bessel type, are promising materials for applications in ultrasonic piezoelectric transducers, exploring as well the radial mode as the thickness vibration modes.
Keywords: Ultra-som; Onda acústica; Transdutor; Polarização; Dispositivos piezoelétricos; CIENCIAS EXATAS E DA TERRA::FISICA